Kecanduan Gadget dan Aktifitas Fisik Pada Remaja: Tinjauan Literatur - Rezky Aulia Yusuf; Musfirah Ramadhani Syamsir; Farihah Muhsana; Andi Sani Silwanah (MEDIA ILMU KESEHATAN, 2022)
Background: Physical inactivity is one of the causes of non-communicable diseases and is a global public health problem. Numerous studies mentioned that teenagers spend their leisure time in engaging sedentary behavior and smartphone addiction is the primary cause of physical inactivity.Objective: This narrative review aims to review the association between smartphone addiction and physical inactivity among adolescents, as well as some solutions that have been carried out to overcome this problem from previous studies. Methods: The search included electronic bibliographic databases from PubMed and Google Scholar, published from 2015-2021. In total, 8 cross-sectional studies met the inclusion criteria of this review.Results: Adolescents who reported being addicted to a smartphone are more likely to engage in sedentary behavior and be physically inactive. Mental health problems such as anxiety, depression, fear, and other mental depression mediated this association. Also, smartphone addiction can be reduced by increasing sports participation and involvement in physical activity among adolescents. Educational institutions and parents can use sports and recreational activities as intervention strategies to overcome smartphone addiction among the adolescent population.Conclusion: This study highlights the association between smartphone addiction and physical inactivity. Physical activity and sports participation may have the potential to prevent smartphone addiction among adolescents.